EFFECT OF SEED SIZE AND SEEDING RATES ON YIELD ATTRIBUTES OF TRITICALE Var. ADMIRAL - Sumaya A. Abdullah; Ahmed S. Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A factorial in randomized complete block design (RCBD), with three replicates, including three seeding rates (200,250, and300seeds.m-2), and three grain size grades of Admiral variety of triticale whole (ungraded), thousand seed weight (TSW) 47.32g, heavy seeds 54.04g and light seeds 40.18g; for two successive growing seasons 2019-2020 and 2020-2021. The results revealed that spike length resembled number of spikelets per spike, grain density and number of grain per spike as seeding rate 200 with whole seeds attained highest value. Great differences between the two seasons were obvious, which was attributed to shortage in rainfall in the second season(407.1mm and 165.4mm). The interaction of seeding rate 200 with heavy size seeds resulted in maximum biological yield (6233 kg.ha-1). The interaction of target seed rate 200 with heavy seeds resulted in maximum grain yield(2895 kg.ha-1). Harvest index was highest value for interaction of seed rate 300 with light seed size which was(4.8). Thousand kernels weight give superior weight for the interaction of rate 200 seeds with heavy grade size(52.02g), the second season was clearly obvious as heavy grade resulted in heavier seeds significantly(14.88g) although it was very small atrophic seeds due to shortage of rainfall. Protein content as percentage was significantly affected by seeding rate, seed grade and their interaction for the first season protein% at 200 seeding rate surpassed other rates(12.04%). Seed grade of whole ungraded seeds resulted in higher protein(12.25%). With respect of the interaction, the highest values was (13.03%) for whole seeds with target rate 200 seeds.m-2.